2018
DOI: 10.3892/etm.2018.6302
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑379 suppresses cell proliferation, migration and invasion in nasopharyngeal carcinoma by targeting tumor protein D52

Abstract: MicroRNAs (miRs) have been demonstrated to be important regulators of malignant behavior in nasopharyngeal carcinoma (NPC) tumorigenesis. The present study aimed to investigate the biological roles and underlying mechanisms of miR-379 in NPC. The study initially observed that miR-379 was significantly downregulated in NPC clinical tissues and cell lines using reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Next, gain-of-function assays were performed on human the NPC cell lines, C666-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…miR-449b-5p suppressed NPC cells malignant phenotype in vitro by inhibiting the expression TPD52. In particular, Zhao et al 31 illustrated that TPD52 knockdown remarkably restrained NPC cells proliferation, invasion and migration. Our paper demonstrated that TPD52 was highly expressed in tumor tissues of NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…miR-449b-5p suppressed NPC cells malignant phenotype in vitro by inhibiting the expression TPD52. In particular, Zhao et al 31 illustrated that TPD52 knockdown remarkably restrained NPC cells proliferation, invasion and migration. Our paper demonstrated that TPD52 was highly expressed in tumor tissues of NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the relationship between miR-379 and various diseases. The majority of these studies suggest that miR-379 plays tumor suppressive role in many types of carcinomas, including nasopharyngeal carcinoma, cervical cancer, lung cancer, gastric cancer, hepatocellular carcinoma, bladder cancer, and osteosarcoma [108][109][110][111][112][113]. With regard to metabolic disorders as described above, de Guia et al revealed a relationship between miR-379 and lipid homeostasis dysregulation [65].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-379, which was also upregulated, is an onco-suppressor miRNA. MiR-379 negatively regulates cell proliferation, migration and invasion in several human cancers, including nasopharyngeal carcinoma 30 , cervical carcinoma 31 , gastric cancer 32 and bladder cancer 33 , by targeting tumor protein D52 ( TPD52 ) , V-crk avian sarcoma virus CT10 oncogene homolog-like ( CRKL ), focal adhesion kinase ( FAK) and mouse double minute 2 (MDM2).…”
Section: Discussionmentioning
confidence: 99%